2021
DOI: 10.3390/jpm11060578
|View full text |Cite
|
Sign up to set email alerts
|

The Downregulation of LSAMP Expression Promotes Lung Cancer Progression and Is Associated with Poor Survival Prognosis

Abstract: Lung cancer has been a leading cause of cancer-related death for decades and therapeutic strategies for non-driver mutation lung cancer are still lacking. A novel approach for this type of lung cancer is an emergent requirement. Here we find that loss of LSAMP (Limbic System Associated Membrane Protein), compared to other IgLON family of proteins NTM (Neurotrimin) and OPCML (OPioid-binding Cell adhesion MoLecule), exhibits the strongest prognostic and therapeutic significance in predicting lung adenocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…LSAMP knockdown led to a significant increase in cell proliferation and viability in the LSAMP wild-type cell lines SH-SY5Y and SK-N-BE(2). These results are in concordance with previous publications (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), suggesting that LSAMP could be a putative tumor suppressor gene also in NB. In addition, re-expression of LSAMP in KELLY cells (with homozygous LSAMP deletion) and overexpression of LSAMP in SK-N-AS cells (with heterozygous LSAMP deletion) inhibited cell proliferation and viability.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…LSAMP knockdown led to a significant increase in cell proliferation and viability in the LSAMP wild-type cell lines SH-SY5Y and SK-N-BE(2). These results are in concordance with previous publications (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), suggesting that LSAMP could be a putative tumor suppressor gene also in NB. In addition, re-expression of LSAMP in KELLY cells (with homozygous LSAMP deletion) and overexpression of LSAMP in SK-N-AS cells (with heterozygous LSAMP deletion) inhibited cell proliferation and viability.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, recurrent alterations in other genes associated with neurodevelopment and NB have recently been described by Lopez et al (17). Notably, LSAMP has previously been described as a tumor suppressor gene in osteosarcoma (33)(34)(35)(36)(37), ovarian cancer (38), renal cell carcinoma (39), prostatic cancer (40,41), epithelioid glioblastoma (42), myeloid leukemia (43) and recently in lung cancer (44). Gene expression analysis among NB cell lines indicated that the average expression levels were lower in LSAMP-rearranged samples, although no statistically significant difference was detected between the groups; however, in the cell line KELLY with a homozygous deletion rearrangement inside LSAMP, no expression levels were detected at exons 1-2 and 2-4.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Chang et al. demonstrated that LSMAP, a tumor suppressor, influences the incidence and progression of lung cancer by regulating the epithelial-mesenchymal transition pathway ( 90 ). C2CD4A is a possible diagnostic marker for colon cancer, and its expression is strongly associated with the tumor stage of colon cancer, which is almost compatible with our results ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…LSAMP (limbic system-associated membrane protein) has been reported to be a candidate tumour suppressor gene in a range of cancer types [44][45][46][47][48]. Interestingly, the downregulation of LSAMP expression in cancer cell lines is associated with poor survival prognosis by promoting lung cancer progression [49]. CALL5 (calmodulin-like protein 5) is also thought to have tumour suppressor activities and is silenced at an early stage of carcinogenesis in squamous cell carcinoma of uterine cervix [50].…”
Section: Discussionmentioning
confidence: 99%